2005
DOI: 10.1016/j.cell.2005.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Receptor Recycling and Degradation by the Endosomal Kinesin KIF16B

Abstract: Different classes of endosomes exhibit a characteristic intracellular steady-state distribution governed by interactions with the cytoskeleton. We found a kinesin-3, KIF16B, that transports early endosomes to the plus end of microtubules in a process regulated by the small GTPase Rab5 and its effector, the phosphatidylinositol-3-OH kinase hVPS34. In vivo, KIF16B overexpression relocated early endosomes to the cell periphery and inhibited transport to the degradative pathway. Conversely, expression of dominant-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
296
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 300 publications
(314 citation statements)
references
References 51 publications
(13 reference statements)
15
296
1
2
Order By: Relevance
“…The plus-end directed motor protein Kif16b, also known as SNX23, is targeted via its PI(3)P-binding PX-domain to early endosomes, dependent on Rab5 and Vps34 activity. Thus, Kif16b is required for endosome positioning and efficient early endosomal recycling (Hoepfner, Severin et al 2005). …”
Section: Figure 3: Tubular Cargo-enriched Subdomains At the Early Sormentioning
confidence: 99%
See 1 more Smart Citation
“…The plus-end directed motor protein Kif16b, also known as SNX23, is targeted via its PI(3)P-binding PX-domain to early endosomes, dependent on Rab5 and Vps34 activity. Thus, Kif16b is required for endosome positioning and efficient early endosomal recycling (Hoepfner, Severin et al 2005). …”
Section: Figure 3: Tubular Cargo-enriched Subdomains At the Early Sormentioning
confidence: 99%
“…Loss of Kif16b, a plus-end directed, PI(3)P-dependent kinesin (Hoepfner, Severin et al 2005), abolished outward transport and resulted in a more concentrated perinuclear localization of TfR without affecting exocytosis. Consistent with (2), depletion of Kif16b together with MTM1 restored perinuclear TfR localization, while it could not rescue the exocytic defect (Figure 27).…”
Section: Pi(3)p Levels Can Be Manipulated By Genetic and Pharmacologimentioning
confidence: 99%
“…Zerial and coworkers (Hoepfner et al, 2005) have recently shown that PI3P generation is not only accompanied by the recruitment of EEA1 but also regulates the loading of the pleckstrin homology domain bearing Kinesin family protein KIF16B. KIF16B is a plus-end-directed motor and mediates transport of early endosomes along microtubules; therefore, it regulates the steady-state distribution of early endosomes (Hoepfner et al, 2005).…”
Section: Pi3k and Cellular Localization Of Geecsmentioning
confidence: 99%
“…These results suggest a mechanism where the level of EEA1 recruitment is important for correct targeting during heterotypic fusion. Inhibition of PI3K activity also inhibits fusion between GEECs, suggesting that similar machinery may function in effecting fusion between GEECs.Zerial and coworkers (Hoepfner et al, 2005) have recently shown that PI3P generation is not only accompanied by the recruitment of EEA1 but also regulates the loading of the pleckstrin homology domain bearing Kinesin family protein KIF16B. KIF16B is a plus-end-directed motor and mediates transport of early endosomes along microtubules; therefore, it regulates the steady-state distribution of early endosomes (Hoepfner et al, 2005).…”
mentioning
confidence: 99%
“…Microtubules are polarised, with the plus-end usually pointing towards the cell membrane, away from the nucleus [40]. There are numerous articles providing supporting evidence as to which motor proteins are involved in each stage of the process, although they do not always agree [3,5,12,23,33]. These differences may be due to the differences in results from the studies of different types of cells, experimental techniques and differences between in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%